Improving your project management skills - Richman, Larry (American Management Association, 2006)
Each year, project managers, certified Project Management Professionals (PMPs(R)) and other project-focused professionals from all over the country enroll in the American Management Association's project management seminars. Based on one of the most popular of these renowned seminars, "Improving Your Project Management Skills" is both a practical reference for beginners and a handy refresher for seasoned professionals
Keywords: Project management.; Gestion de projet.; TECHNOLOGY & ENGINEERING -- Project Management.; BUSINESS & ECONOMICS -- Project Management.; Project management; Electronic books.